IDENTIFICATION OF LOCATION ALLOWANCE ZONE FOR BANK SYARIAH "X" OUTLETS USING ORDINAL LOGISTIC REGRESSION - Aldinda Albanna; Yekti Widyaningsih (Jurnal Statistika dan Aplikasinya, 2025)
Companies need good human resources to achieve their goals, one of which is by providing rewards, such as location allowances. Bank Syariah "X" is one of the institutions that provides location allowance, which is an allowance based on the employee's work location. This policy was last established in 2021, therefore adjustments are needed. This study aims to analyze the factors that explain the determination of location allowance zoning and predict the zoning of new outlet location allowances. Location allowance zoning is determined based on the factors of cost, remoteness, and location access. Factors that are thought to represent these three factors and influence the determination of location allowance zoning are the consumer price index (CPI), human development index (HDI), construction cost index (CCI), infrastructure pillar index (IPI), outlet distance to the nearest health center (ODHC), and outlet distance to the nearest primary school (ODPS). The location allowance zoning consists of three categories with an ordered nature. Based on the research objectives and the type of dependent variable, the method used was ordinal logistic regression. This research produces factors that explain the determination of location allowance zoning, namely CCI, IPI, and ODHC with 70% accuracy and balanced accuracy for Zone 1, Zone 2, and Zone 3 & 4, respectively 81.2%, 70.8%, and 76.7%. Based on the initial policy data of Bank Syariah "X", the model misclassified 35.6% of outlets.